The role of new media in shaping a creative environment for regional development - Suchacka, Małgorzata; Zawojski, Piotr (Creativity Studies, 2022)
Progressive technologization of society has an impact on an innovative approach to art and culture. New media play an important role in this context by shaping the environments of creative people who refer to regional resources in their work. The main purpose of the paper is to analyse selected theoretical concepts covering the issues of the use of new media art in the context of a symbiotic relationship with the creative environment of the region. The authors use the method of literature analysis and an interdisciplinary synthesis of the achievements of social sciences and humanities. The theoretical assumptions presented before are illustrated by the reference to a part of wider authors’ sociological research – expert debates in the environment of regional creators of new media art. The conclusions indicate potential development trends and especially promising directions for further activities in the field of using new media in shaping the creative environment.